Authoritarian Leaders Share Conspiracy Theories to Attack Opponents, Promote In-Group Unity, Shift Blame, and Undermine Democratic Institutions - Zhiying Ren; Andrew M. Carton; Eugen Dimant; Maurice E. Schweitzer (Center for Economic Studies and ifo Institute (CESifo), 2022)
Although many virtuous leaders are guided by the ideal of prioritizing the need and welfare of their subordinates, others advance their self-interest at the expense of the people they purport to serve. In this article, we discuss the relationship between leadership and the spread of conspiracy theories. We propose that leaders spread conspiracy theories in service of four primary goals: 1) to attack opponents; 2) to increase support from their ingroup members; 3) to shift blame and responsibility; and 4) to undermine institution that threaten their power. We argue that populist and conservative leaders are most likely to spread conspiracy theories during periods of instability.
Keywords: 330; conspiracy theories sharing; leadership; authoritarian leaders